Digital Marketing Communication Strategies to Boost Visitor Interest at Grande Garden Cafe Through Social Media - Anugrah, Teguh Putro; Andaresta, Larasati (Universitas Pendidikan Nasional, 2023)
The cafe business in Indonesia is currently experiencing rapid growth. Each cafe possesses its own distinct characteristics aimed at attracting customers. Given the proliferation of cafes across Indonesia, business owners are compelled to devise distinct strategies for promoting their enterprises to gain broader recognition. One approach is employing social media as a promotional medium. In the contemporary era, numerous business owners utilize social media platforms as a means of advertising. Just like Grande Garden Cafe, which has opted for social media channels to connect with their customer base. Through these platforms, Grande Garden Cafe showcases its products, highlights its activities, and promotes its special offers. The cafe also generates trending content, skillfully packaged to capture the audience's interest and ultimately motivate them to visit the establishment. The rapid advancement of information technology now serves not solely as a means of communication but significantly influences nearly all facets of life, including the business domain. The ensuing impact can lead to the proliferation of businesses on a large scale, with many entrepreneurs consistently highlighting their unique advantages. Consequently, this intensifies the level of competition faced by all stakeholders, particularly companies as producers. In response, companies must be astute in formulating and comprehending the prevailing conditions to determine diverse marketing strategies. In order to remain competitive, businesses must find ways to distinguish themselves and raise awareness of market opportunities, even when operating with limited resources. Utilizing social media is a judicious choice in attaining this objective due to its practicality, cost-effectiveness, and capacity for facilitating consumer sharing and interaction.